Rate and Type of Infections in Children with Nephrotic Syndrome - Mohammed, Doaa Youssef; Selim, Mona Shaaban Ali; Zeid, Ali Mohammed Abo; Neemat-Allah, Mayy Abd Alfattah (Archives of Clinical and Medical Case Reports, 2018)
Introduction: Changes in immunity are complex in nephrotic syndrome, affecting the cellular and humoral balance of specific immunity which may impair response to infection, currently recognized that at least half of relapses are triggered by infection. We aimed to describe the accurate rate of infection and specific type of treatment in nephrotic syndrome cases admitted with activity to nephrology unit. Subjects and methods: This is a cross-sectional, case control study performed among 90 cases admitted nephrotic syndrome with activity, they were two group; group I 60 admitted with infection and group II 30 nephrotic syndrome admitted without infection. They were evaluated for the activity of disease, type of infections, occurrence of complications and fate of therapy and routine laboratory tests were done. Result: The most common type of infection was gastroenteritis (GE) (25%) of infected cases , 2nd most common Then Urinary tract infection (UTI) (21.7%), While Pneumonia represented (15%) of infection. there was no significant pathogen in (61.66%), the most common pathogen is E.coli (25%), followed by Shigella (6.66%), pneumococci (3.33%), klebsiella (1.66%) and proteus (1.66%) of all infected cases. The most frequently used antibiotic before culture is Ampicillin, sulbactam followed by cefotaxime and after culture Cefepime, Meronem, ceftazidime and Vancomycin. Conclusion: We concluded that 66.6% of admitted children with NS with relapse were due to infection, the most common type of infection is gastroenteritis, followed by Urinary tract infection, Viral infection represents high rate of infected cases and the most common type of bacteria after culture is E.coli, Shigella, pneumococci.